Diplomasi Indonesia dalam Penanganan Kasus Wilfrida Soik di Malaysia Tahun 2010-2015 - Dewi, Ardillah Fauziyyah; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
This research discusses about Indonesian diplomacy of Wilfrida Soik case in Malaysia on 2010-2015. Wilfrida Soik is an Indonesian worker who is threatened with a death penalty because of a murder case committed to her employer. This research aims to explain the problems of Indonesian workers in Malaysia which focus on Wilfrida Soik case. Diplomacy is also carried out by Indonesian government to liberate Wilfrida Soik from the death penalty in Malaysia since 2010. This research analyses Indonesia's diplomacy efforts through the government and related parties by using multi-track diplomacy and protection diplomacy concepts. This research uses qualitative research methods and data collection techniques through literature studies and interviews. The final results of this research showed that Indonesian diplomacy in Wilfrida Soik case was carried out through diplomacy efforts by the government, legal assistance and advocacy efforts by Migrant CARE. The multi-track diplomacy in the Wilfrida Soik case was conducted through nine channels, those are government, NGOs, business, citizens, education, activists, religious activities, fundraising and communication in the form of public opinion. The actions from Indonesian government and various non-governmental entities was indirect attempts to absolve Wilfrida Soik from the verdict. It is categorized as indirect due to the independent decision of the High Court which cannot be contested. Thus the liberation attempts from those entities need to be affecting the decision of the Malaysian High Court. The efforts of the Indonesian government and various non-governmental entities in conducting protection diplomacy fulfill several aspects of multi-track diplomacy, so that the efforts made by the government had achieved the goals of diplomacy in the Wilfrida Soik case.